MOTIVATION OF COGNITIVE INTEREST IN PHYSICAL THEORIES - Ligai, M.A.; Ermekova, Zh.K. (Recent Contributions to Physics, 2018)
Suggested рареr is not just vital with the rapid decrease of students’ interest in thorough and proper sciences, and also with the lack of specialists for realization of innovative technologies in our dynamically developed country. Besides, it is probably interesting for all teachers, who presents the natural sciences, whose achievements are on the basic of all technologies and important for production, economy and etc. To sum up, the development of informative interest to all natural sciences is the most important task in educational process.